Developing a software process simulation model using SPEM and analytical models. (10th March 2009) - Park, Seunghun; Kim, Hyeonjeong; Kang, Dongwon; Bae, Doo-Hwan
To develop Software Process Simulation Models (SPSMs) more effectively, we need to consider the following issues: reducing the knowledge difference between increasing the reusability of a simulation model, decreasing the complexity of a simulation model, and mitigating the lack of historical data. We propose an approach to develop an SPSM based on SPEM, and widely adopted analytical models. An SPEM-based process model is integrated with the quantitative information and transformed into a DEVS-Hybrid SPSM. Our approach resolves the issues by the transformation algorithms, the hierarchical and modularised modelling properties of SPEM and DEVS, and widely adopted analytical models.